Prioritizing support for expanding the Family Life and HIV Education curriculum: An overview of expanded-FLHE pilot activities in Nigeria. - Adebayo, Emmanuel; Nwokocha, Ezebunwa; Antigha, Emma Bassey; Mohammed, Zainab; Adeyemi, David; Fasawe, Olufunke; Wiwa, Owens (International Journal of Child & Adolescent Health, 2023)
Since 2003, The Family Life and HIV Education (FLHE) curriculum (now referred to as Family Life Health Education) has represented Nigeria's attempt at a national comprehensive sexuality education (CSE) program. The 2003 FLHE curriculum has been implemented on a national scale but has never had a full review or been updated to meet recent evidence-informed global standards (i.e., UNESCO 2009, 2018). Given the limitations raised in a 2013 evaluation of the curriculum based on UNESCO's International Technical Guidance on Sexuality Education (2009), the Clinton Health Access Initiative (CHAI), in partnership with the Federal Ministry of Education (FMoE), developed an expanded version of the 2003 FLHE curriculum. This expansion aligns to the most up-to-date global best practices, while remaining contextually relevant, to better respond to the sexuality education needs of adolescent girls and boys aged 10 to 18 years of age in Nigeria. CHAI is supporting four states in Nigeria to pilot an Expanded-FLHE curriculum. This article presents key activities and lessons learned from CHAI's effort in conducting the Expanded FLHE curriculum pilot in selected schools across its Sexual and Reproductive Health (SRH) programs and areas of implementation in Kano, Katsina, Kaduna and Rivers states.